The Legal Reasoning of Religious Court Judges in Granting Marriage Dispensations from the Perspective of Maqāshid Al-Shari’ah - Ahmad Baihaki; Rabiah Al Adawiah (KRTHA BHAYANGKARA, 2024)
The issue of preventing child marriage and marriage dispensation to provide child protection remains a crucial legal problem. This research aims to examine the legal reasoning in the rulings of Religious Court judges regarding marriage dispensation applications and to what extent these rulings provide child protection from the perspective of Maqāshid Al-Shari’ah. This study employs normative legal research methods and analyzes legal issues from the perspective of Maqāshid Al-Shari’ah. Data collection was conducted through a literature review. The findings indicate that the legal reasoning in the rulings of Religious Court judges has not fully aligned with the spirit of the Marriage Law, the Child Protection Law, and the Supreme Court Regulation on Marriage Dispensation, which aim to prevent child marriage. There is a dilemma among judges between efforts to prevent child marriage and the legal reality where the child applying for marriage dispensation has met urgent reasons and supporting evidence. Most of the rulings by Religious Court judges on marriage dispensation cases align with the main objectives of Islamic law (Maqāshid Al-Shari’ah), which are the protection of religion (hifz al-din), the protection of life (hifz al-nafs), the protection of lineage (hifz al-nasl), the protection of intellect (hifz al-aql), and the protection of property (hifz al-māl).